Mendekonstruksi Ciptaan: Sebuah Tafsir Ayub Pasal 3:1-26 - Emanuel Gerrit Singgih (Faculty of Theology Duta Wacana Christian University, 2018)
Abstract In this article the conventional image of the character of Job as patient and trusting in face of a series of calamities, and such receives back all that he has lost before as can be found in the prologue (chapters 1-2) and the epilogue (chapter 42) of the Book of Job, is contrasted with the character of Job in chapter 3, in which Job is pictured as facing the end of everything, including the end of his life himself. For him it is the end of the world, the collapse of creation, or better, the return of creation to chaos. That is why the title contained the term “deconstruction”, and by employing the theory of deconstruction, the stages where Job is deconstructing creation are described and analysed. Abstrak Pemahaman yang agak umum mengenai karakter Ayub yang sabar dan tawakal sebagaimana dihayati berdasarkan pendahuluan (prolog) dan penutup (epilog) kitab Ayub, dan karena itu pada akhirnya mendapat pemulihan, dipertentangkan dengan karakter Ayub dalam pasal 3, yang sungguh-sungguh menggambarkan sedang menghadapi akhir dari segala-galanya bagi dirinya, bagaikan sebuah kiamat. Dunia ciptaan baginya sudah berakhir, atau lebih baik, ciptaan telah kembali menjadi khaos. Maka di sini dipergunakan istilah